The writing on the wall - Henry R Bourne (eLife, 2013)
The biomedical research enterprise in the US has become unsustainable and urgent action is needed to address a variety of problems, including a lack of innovation, an over-reliance on soft money for faculty salaries, the use of graduate students as a source of cheap labour, and a ‘holding tank’ full of talented postdocs with limited career opportunities.